2018
DOI: 10.1016/j.sleh.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration mediates the relationship between health behavior patterns and obesity

Abstract: Our results indicate that health behavior patterns mediated by sleep duration may influence a child's %BMI. The bi-directionality of the relationship between health behaviors and sleep remains unclear. Our findings suggest the importance of a constellation of health behaviors on childhood obesity. Interventions should include a multitude of health behaviors and consider the possibility that improving diet and activity behaviors may facilitate improved sleep and lowered obesity risk among children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(40 reference statements)
1
14
0
1
Order By: Relevance
“…Several child and adolescent studies have assessed the association between sleep measures and dietary intake including FV consumption [52,53,54,55,56,57,58,59,60,61,62,63,64,65]. The association was shown to be positive in a recent meta-analysis [66].…”
Section: Sleep and Fruit And Vegetable Consumptionmentioning
confidence: 99%
“…Several child and adolescent studies have assessed the association between sleep measures and dietary intake including FV consumption [52,53,54,55,56,57,58,59,60,61,62,63,64,65]. The association was shown to be positive in a recent meta-analysis [66].…”
Section: Sleep and Fruit And Vegetable Consumptionmentioning
confidence: 99%
“…Previous studies have suggested that PA and diet are critical components of healthy lifestyle behaviors, linking not only sleep quality but also the QoL [ 6 , 7 , 8 , 9 , 10 ]. Evidence has also indicated the critical role of sleep quality in mediating the effect of PA and/or diet on maintaining good health [ 11 , 12 , 13 ]. Gothe et al proposed that a novel sleep and QoL model is useful to design new health interventions by targeting PA to promote sleep quality, which, in turn, influences the QoL [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bravo et al, 2016, 2018; Kimmes et al, 2017; Pearson et al, 2015). Although the AWE supported a one-profile model, Kaar et al (2018) note that the fit statistic best serves as a lower bound due to under-extraction, thus, it was concluded that the evidence best supported the 3-profile model depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 92%